Cystatin C as a Maker of the Renal Function: an Alternative - Alexander Benavides Couto; Javier Martínez Navarro (Universidad de las Ciencias Médicas de Cienfuegos, 2018)
The precise assessment of the renal function level is essential for identifying and managing renal chronic disease, but the first stages of this condition is silent and not identified with routine tests. Measuring cystatin is useful for the early detection of renal disease, especially when other tests or parameters do not yet show alterations and even before symptoms and signs appear. It´s concentration is not influenced by age, sex, or protein intake and presents a higher sensitivity to slight changes in glomerular filtration. Due to its properties, cystatin C is a useful laboratory parameter in the diagnosis and prognosis of primary renal disease or related to other diseases, which secondarily cause kidney lesion.